Випадок первинного гіперпаратиреозу - Станкова, Н. І.; Ляшук, П. М.; Грабовецький, О. В.; Ляшук, Р. П. (Clinical Endocrinology and Endocrine Surgery, 2009)
The article deals with a clinical case of primary hyperparathyroidism caused by adenoma of parathyroid gland. The difficulty of prompt diagnosis consisted in the fact that the disease was combined with iatrogenic hypercortisolism, symptoms of which had many features in common with the main pathologic process.